2020
DOI: 10.1097/brs.0000000000003460
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spine Endplate Abnormalities and Association With Pain, Disability, and Adjacent Segment Degeneration After Anterior Cervical Discectomy and Fusion

Abstract: Study Design. A retrospective study with prospectively-collected data. Objective. To determine how type, location, and size of endplate lesions on magnetic resonance imaging (MRI) may be associated with symptoms and clinical outcomes after anterior cervical discectomy and fusion (ACDF). Summary of Background Data. Structural endplate abnormalities are important, yet understudied, phenomena in the cervical sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
0
15
1
Order By: Relevance
“…Based on their results, the authors proposed that endplate defects were the initiating factor that triggered a cascade of degradation that results in degenerative disc disease, which may precede the development of clinical symptoms. Although several studies have found that MC and endplate abnormalities may be related to axial neck pain, 15,16,20 as well as low back pain, 11,13,45 the present study found no association between any of the imaging groups and preoperative neck pain. These findings should be taken with special consideration as our control group had significant neck pain at baseline, which may have masked associations with pain and imaging phenotypes.…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…Based on their results, the authors proposed that endplate defects were the initiating factor that triggered a cascade of degradation that results in degenerative disc disease, which may precede the development of clinical symptoms. Although several studies have found that MC and endplate abnormalities may be related to axial neck pain, 15,16,20 as well as low back pain, 11,13,45 the present study found no association between any of the imaging groups and preoperative neck pain. These findings should be taken with special consideration as our control group had significant neck pain at baseline, which may have masked associations with pain and imaging phenotypes.…”
Section: Discussioncontrasting
confidence: 80%
“…In a previous study of the same group of patients, both typical and atypical endplate abnormalities were associated with myelopathy and upper extremity sensory deficits. 21,20 There is still not much understood regarding specific phenotypes and their impact on the transition from pure spondylosis to a spondylotic myelopathy. As described above, much of the lumbar research on MC and endplate anatomy has been focused on back pain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations